The tyranny of the definite article: some thoughts on the art of intellectual history - Young, B (Elsevier, 2002)
This essay argues, following an insight of Burckhardt, that the philosophy of history is a 'centaur', and that is has a tendency to hinder rather than to encourage the practice of history. It challenges many of the presuppositions of Bevir's study, demonstrating that The Logic of the History of Ideas is not, in any meaningful sense, an historically minded work. The 'logic' of the essay looks to the arts, especially literature and music, as providing genuinely illuminating parallels to the discipline involved in the practice of intellectual history. History cannot be understood as a process of philosophical abstraction; pertinent examples are of its essence, and plurality is therefore central to its richly textured nature. It still has much to learn from the reflexive procedures of anthropology. By examining the idea of 'tradition' the essay demonstrates that 'the past' is never dead, and that the relationship between texts is a living process: the intellectual historian is him/herself an artist, and his/her task is no less demanding than that of the creative artist, and it is always humblingly provisional.